Novas estratégias para aprimoramento da eficiência em deionização capacitiva: simulação numérica, estudo de célula e aplicação de campo magnético externo - Luz, Felipe Staciaki da (Universidade Federal de São Carlos, 2025)
Capacitive deionization (CDI) has emerged as a promising electrochemical technology for desalination due to its low energy consumption, simple design, and potential for integration with renewable energy sources. However, its scalability and performance are still limited by challenges such as electrode saturation, co-ion repulsion, and slow adsorption kinetics. This thesis presents an integrated approach to enhance CDI performance through the development of new cell configurations, experimental evaluation, and multiphysics simulations. Particular focus was given to the application of ionic diodes and magnetic fields as tools to intensify ion removal and improve process continuity. Ionic diodes were implemented to promote directional ion flow and mitigate electrode saturation, resulting in significant increases in salt adsorption capacity (SAC) and overall system efficiency. The effect of dimensional and operational parameters was systematically investigated, revealing complex interactions governing mass transfer and energy efficiency. Furthermore, this work explored magnetohydrodynamic-assisted CDI, where the application of a magnetic field in conjunction with the electric field induced convective motion via the Lorentz force, intensifying ion transport and accelerating adsorption kinetics. Experimental results, supported by numerical simulations, demonstrated that the application of a magnetic field accelerates the electrosorption process and increases the amount of ions removed from water. The findings presented in this study provide important contributions to the understanding of the physical phenomena governing CDI and propose effective strategies to advance the technology toward sustainable desalination systems, particularly for brackish water treatment.
New strategies for enhancing the efficiency of capacitive deionization: numerical simulation, cell study, and application of an external magnetic field
Keywords: Dessalinização eletroquímica; Método dos elementos finitos; Diodos iônicos; Efeito magnetohidrodinâmico; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; 6. Água Potável e Saneamento